Pelatihan Manajemen Keuangan pada UMKM Produk Olahan Nanas di Desa Babadan Kecamatan Ngancar Kabupaten Kediri - Nastiti Winahyu; Ferica Agustin; Sandra Dwi Angesti (Institut Pertanian Bogor, 2022)
Pineapple (Ananas comosus (L.) Merr.) is one of the leading agricultural commodities in Babadan Village, Ngancar District, Kediri Regency. The use of pineapples that are not included in the sales grade in terms of size and maturity level encourages people to seek processed products based on pineapple commodities. Business development can be supported by providing financing from a local cooperative, namely Koperta Langgeng Mulyo. Prospective tenants of cooperatives are Family Welfare Development (PKK) members. Micro, Small and Medium Enterprises (MSMEs) that are run include juice, dodol, and pineapple jam. Problems by participants included no financial recording activity and evaluation of the feasibility of business conditions, so financial management training became the solution. The activity was attended by 20 participants with material on socializing the importance of financial and inventory management, business feasibility, and strategies to enter the modern market. The results of the evaluation showed that the average knowledge of the participants increased from 48% (pre-test) to 75% (post-test).